2022
DOI: 10.3390/aerospace9030142
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Approach for Impulsive Formation Maintenance Relevant to Distributed SAR Missions

Abstract: This paper proposes an approach for impulsive formation maintenance tailored to distributed synthetic aperture radar, i.e., a spaceborne system composed by several antennas working together to provide enhanced remote sensing capabilities. The analyzed configuration is designed to guarantee the presence of a safety tube surrounding each satellite as the dynamics evolve. Formation requirements are related to general constraints on the acceptable along-track and radial/cross-track separations. The paper introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Synthetic aperture radar (SAR) satellites can acquire images of specified areas of the Earth’s surface at observation requests with all-day and all-weather imaging capacity [ 1 , 2 ]. Image products acquired by SAR satellites are widely used in many fields, such as emergency response in environments [ 3 ], target recognition and classification [ 4 ], urban planning and architectural layout [ 5 ], and crop detection and disaster prevention [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic aperture radar (SAR) satellites can acquire images of specified areas of the Earth’s surface at observation requests with all-day and all-weather imaging capacity [ 1 , 2 ]. Image products acquired by SAR satellites are widely used in many fields, such as emergency response in environments [ 3 ], target recognition and classification [ 4 ], urban planning and architectural layout [ 5 ], and crop detection and disaster prevention [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high-precision control of satellites is conducive to the completion of satellite missions. In some current studies, the high-precision formation satellite flight control is mainly based on the consistency collaborative control [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [10] designed a fault-tolerant controller based on sliding mode cooperative control and showed that the proposed control method tolerates the actuators' faults and controls the satellite's attitude while desaturating the reaction wheels. Reference [11] proposed a coordinated control to fulfil these constraints for impulsive formation maintenance tailored to distributed synthetic aperture radar.…”
Section: Introductionmentioning
confidence: 99%